Housing and accessibility after the COVID-19 pandemic: Rebuilding for resilience, equity and sustainable mobility - Valenzuela-Levi, N.; Echiburu, T.; Correa, J.; Hurtubia, R.; Muñoz, J.C. (Transport policy, 2021)
A more sustainable post COVID-19 world requires urban transport policies aiming for resilience, social equity and decarbonisation. Instead of just focusing on the transport sector, the authors propose an integrated approach to housing and mobility. This approach acknowledges the challenges posed by inadequate housing and dependence on motorised transport during the COVID-19 crisis. In contrast, adequate housing and cycling became paramount resources while confronting the pandemic. Using Santiago de Chile as a case study, this research examines how different relocation scenarios for its current housing deficit cannot only affect the ability to implement stay-at-home measures, but also the potential of cycling as a relevant commuting alternative. The current location of the families suffering this deficit is compared to three scenarios: compact, pericentral and extended. In light of the learnings from the COVID-19 crisis, a housing-cycling policy becomes a tool for resilience; equity is achieved by enforcing the right to housing, by increasing job opportunities among the poor, and by reducing the dependence on expensive motorised transport; decarbonisation is achieved by promoting active transportation and reducing the dependence on motorisation. •Both adequate housing and active transportation enable physical distancing during a COVID19-type pandemic.•An integrated housing and cycling policy is proposed and modelled in Santiago de Chile.•Subsidised housing is located according to potential cycling-to-work accessibility.•Potential cycling trips are modelled in three scenarios of relocation of the current housing deficit.